Effects of varying weld speeds on the microstructure, mechanical properties, and corrosion behavior of clad rebars in a marine environment - Zecheng Zhuang; Weiping Lu; Zhe Gou; Lei Zeng; Xuehai Qian; Rifeng Wang; Erte Lin; Zhen Li; Yong Xiang; Jianping Tan (Scientific Reports)
Abstract The welding parameters of the clad rebar were established to guide the new type of bimetal steel application on the marine construction. Four different welding speeds of 0.4 mm/s, 0.6 mm/s, 0.8 mm/s, and 1.0 mm/s were utilized to weld the clad rebars. The microstructural changes, such as grain size, geometric necessary dislocation density, dynamic recrystallization, and grain orientation, were measured using the backscatter diffraction (EBSD) technique. The mechanical characteristics of welded specimens at four welding speeds were measured using the Vickers hardness test. An electrochemical corrosion test was conducted to detect the corrosion resistance of the weld metal at four welding speeds, and the corrosion morphology and element distribution were observed using scanning electron microscopy. The results depict that with the augment in welding speed, the number of grains increases gradually, and grain thinning occurs in both the weld metals and the base metals. The maximum number of dynamic recrystallizations occurs when the welding speed is 0.6 mm/s. After the electrochemical corrosion test, the best corrosion resistance is observed when the welding speed is 0.6 mm/s. Combining the analysis of microstructure, mechanical characteristics, and corrosion resistance, it is found that the optimal welding speed among the four tested is 0.6 mm/s. Hence, selecting the most proper weld parameters is necessary, moreover, it offers a solid foundation for researching the subsequent weld process system of the clad steel bars.